A wind power comparison between Costa Rica and the rest of the world - Richmond-Navarro, Gustavo (2022)
Wind turbine installations continue to grow throughout the world and play an important role in the way the world is powered. This study analyses the growth of wind energy in the most important regions of the world and make a comparison with Costa Rica. The regions of the study include Europe, United States, China and Latin America. This article is also intended to show Costa Rica’s investments in terms of building and maintenance of wind farms. There is a relationship between the costs of installing and maintaining wind farms and the development of installed wind capacity. For the sake of clarity, a real example from Tejona’s Costa Rica wind farm is provided. This analysis shows that Costa Rica is a leader in wind energy in Central America and also stands out in the Latin American region and the Caribbean, but needs to overcome some challenges in the economy and costs related to wind energy to achieve higher goals in wind power production.